2014
DOI: 10.1177/0145445514521232
|View full text |Cite
|
Sign up to set email alerts
|

Video Self-Modeling

Abstract: The current study investigated the effects of a Video Self-Modeling (VSM) intervention on the compliance and aggressive behavior of three children placed in a psychiatric hospital. Each participant viewed brief video clips of himself following simple adult instructions just prior to the school's morning session and the unit's afternoon free period. A multiple baseline design across settings was used to evaluate the effects of the VSM intervention on compliance with staff instructions and aggressive behavior on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In one study (Foley-Nicpon et al, 2017), it was unclear which measure/ methods were used for self-reported ADHD. Comorbid conditions reported in participants with ADHD across the studies were oppositional defiant disorder (Axelrod et al, 2014;Sibley et al, 2012;Wilkes et al, 2011;Wilkes-Gillan et al, 2014b, 2016 and mild intellectual disability (Embregts, 2002). Participants' medication use/status was reported in all except two studies (Embregts, 2002;Foley-Nicpon et al, 2017).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study (Foley-Nicpon et al, 2017), it was unclear which measure/ methods were used for self-reported ADHD. Comorbid conditions reported in participants with ADHD across the studies were oppositional defiant disorder (Axelrod et al, 2014;Sibley et al, 2012;Wilkes et al, 2011;Wilkes-Gillan et al, 2014b, 2016 and mild intellectual disability (Embregts, 2002). Participants' medication use/status was reported in all except two studies (Embregts, 2002;Foley-Nicpon et al, 2017).…”
Section: Participantsmentioning
confidence: 99%
“…Eight studies reported using rating scales (e.g., Conner's rating scales) based on the International Diagnostic and Statistical Manual of Mental Disorders 3rd and 4th edition with parent and/or teacher reports to confirm ADHD symptomology. Two studies did not report the use of a screening tool to confirm ADHD symptomology of participants (Axelrod et al, 2014;Embregts, 2002). In one study (Foley-Nicpon et al, 2017), it was unclear which measure/ methods were used for self-reported ADHD.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…& Williams, 1994; Mace et al 1988); graduated guided compliance (Wilder et al, 2012); a package of antecedent interventions (proximity, posture, eye contact, attention and response interruption; Stephenson & Hanley, 2010); and video self-modeling (Axelrod, Bellini & Markoff, 2014), among others. Although these interventions have been shown to improve compliance, and none has significant limitations, some can be time consuming to implement or impractical (e.g., video self-modeling requires multiple video clips to be made of the child that capture the child being compliant in multiple contexts and video viewing prior to evaluation of the intervention; Axelrod et al, 2014).…”
mentioning
confidence: 99%
“…& Williams, 1994; Mace et al 1988); graduated guided compliance (Wilder et al, 2012); a package of antecedent interventions (proximity, posture, eye contact, attention and response interruption; Stephenson & Hanley, 2010); and video self-modeling (Axelrod, Bellini & Markoff, 2014), among others. Although these interventions have been shown to improve compliance, and none has significant limitations, some can be time consuming to implement or impractical (e.g., video self-modeling requires multiple video clips to be made of the child that capture the child being compliant in multiple contexts and video viewing prior to evaluation of the intervention; Axelrod et al, 2014). Others employ aversive procedures that may produce pain (spanking; Forehand & McMahon, 1981) or possible emotional distress such as a loud scolding voice or visual glare (Doleys et al, 1976), or have relatively long latencies to reach target levels of compliance (e.g., seven treatment sessions to increase compliance above 80%; Rortvedt & Miltenberger, 1994).…”
mentioning
confidence: 99%